Perancangan dan Implementasi Kelas Virtual FILKOM Universitas Brawijaya dengan Memanfaatkan Teknologi WebRTC (Web Real-Time Communication) - Rahadiyan Yuniar Rahmanda; Eko Sakti Pramukantoro; Widhi Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Streaming and video conferencing technology can be utilized to implement distance learning technology such as virtual class. One of platforms that can be used in developing a virtual class is WebRTC. This research intends to design and implement virtual class system for FILKOM UB by utilizing WebRTC, which offers solutions to distance learning methods that lecturers and students can do whenever and wherever through the web in real-time. 3 main features of this virtual class are a broadcast feature that allow lecturer to do broadcasting to students, share file feature that allow lecturer to send files to students, and text-chat feature that allow lecturer and students can send chat messages. This research perform functionality testing and results that all of system requirements have been fulfilled in accordance with the analysis of system requirements. This research also perform system network performance testing especially on broadcast feature to know quality of service (QoS) from system. This test results show that highest average delay value on audio delivery is 143.17 ms and video is 198.82 ms. Highest average jitter value on audio delivery is 240.51 ms and video is 134.67 ms. Average packet loss on audio or video delivery is well below 1%.